Impact of Covid 19 on the Expat Anticipation - A case study from Sultanate of Oman - Dr.Ananth.A, Ali.O.P (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The COVID 19 pandemic has affected the entire world as many countries restricted their economic activity, travel and tourism. It creates an impacton expatriates and their families around the world. The aim of research is to find out the anticipation of expats as many people were lost their job during the pandemic. This research is a qualitative and exploratory research in which primary data is used which is collected through an online survey from more than 200expats who are working in industries and educational sectors in Sultanate of Oman.A structured questionnaire was used to collect the responses. Pilot study was conducted to identify the factors that influence expat anticipation. Statistical tools such as factor analysis and multiple regression was used to draw meaningful conclusion. SPPS and AMOS 21 statistical packages were used to analyze the data.This study used factors which explored from the literatures as Migration, Remittance, Family concern, Job security, Consumption pattern and Investment attitudes influencing the expat anticipation. The collected data made group analysis based on income category and explored significant results that the low income group those are earning less than 250 OMR per month are concerning about their consumption pattern, the high income group earning more than 1500 OMR concerning about their family and the earning between 1000 to 1500 OMR are concerning about migrating to home country.